LEARNING EQUITY IN A UNIVERSITY CLASSROOM - van der Westhuizen, GJ (South African Journal of Higher Education, 2016)
Since 1994, education policy documents in South Africa have prioritised the goal of equity in education, understood as increased access to programmes, more equitable staff and student profiles, and curricula that are more responsive to the needs of all students. The challenge of effecting the goal of equity at levels of teaching and learning in university classrooms still remains. This article therefore focuses on notions of ‘learning equity’ in an attempt to problematise the need for equity at the level of teaching and learning. The purpose is to use a learning theory perspective to develop a deeper understanding of the challenges of equity in practice in order to make recommendations for a more responsive and responsible pedagogy in university environments. Based on an analysis of equity theory, this article develops an understanding of what equitable learning could entail. Drawing on situated learning theory as espoused by Brown, Collins and Duguid (1998), Rogoff (1990) and others, a framework was developed in terms of which situated learning could be meaningfully facilitated. This framework is used to analyse the scope for learning equity in a specific undergraduate course in Education. From the analysis it is concluded that a careful consideration of learning situations, learning activities, semiotic tools, and the various trajectories students find themselves in open up spaces and options for the facilitation of more equitable learning. The article contributes to the argument that learning theory perspectives allow closer analyses of the challenges of equitable learning.